Search for direct pair production of supersymmetric partners to the tau lepton in proton-proton collisions at root s=13TeV - (:unkn) unknown (SPRINGER, 2020)
A search is presented for t slepton pairs produced in proton-proton collisions at a center-of-mass energy of 13 TeV. The search is carried out in events containing two t leptons in the final state, on the assumption that each t slepton decays primarily to a t lepton and a neutralino. Events are considered in which each t lepton decays to one or more hadrons and a neutrino, or in which one of the t leptons decays instead to an electron or a muon and two neutrinos. The data, collected with the CMS detector in 2016 and 2017, correspond to an integrated luminosity of 77.2 fb-1. The observed data are consistent with the standard model background expectation. The results are used to set 95% confidence level upper limits on the cross section for t slepton pair production in various models for t slepton masses between 90 and 200 GeV and neutralino masses of 1, 10, and 20 GeV. In the case of purely left-handed t slepton production and decay to a t lepton and a neutralino with a mass of 1GeV, the strongest limit is obtained for a t slepton mass of 125 GeV at a factor of 1.14 larger than the theoretical cross section.
Keywords: E(+)E(-) COLLISIONS; MEASURING MASSES; SCALAR LEPTONS; MODEL; EXTENSION; INVARIANT